From the Agora to the Algorithm : Aristotle's rhetoric as a framework for understanding social media persuasion : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Albany, New Zealand - Nelson, Nick (Massey University, 2026)
Originally developed to connect people, social media created a new digital space where communities could be built, social networks established, and user generated content created and rapidly shared. Celebrated as a hallmark of progress, the rise of these platforms held great promise for society and were celebrated as providing a new public-commons where democracy could flourish. More recently, however, this capability has been co-opted by governments, political parties, and other organisations to exert power both domestically and internationally, and manipulate others in the pursuit of military, political, and societal goals. This is altering the geopolitical balance of power; polarising societies; creating uncertainty and anxiety; and undermining trust in knowledge, people, systems, and institutions. No longer then is social media merely a tool to bring people together; rather, it is being utilised as a persuasive device to threaten security at the individual, societal, national, and international levels. Understanding this problem and, in particular, understanding how persuasive attempts occur in the digital environment, is, thus, of considerable importance. While research has made considerable gains in understanding how various factors are exploited to effect online persuasion, a gap in our understanding of persuasion in this particular environment remains, particularly as it impacts issues of national security. This thesis argues that drawing on Aristotle’s rhetorical framework and reframing it for the contemporary environment, a more comprehensive understanding of persuasive attempts online can be gleaned. Utilising a psychological humanities approach and a rhetorical framework, this thesis undertook an analysis of two cases to understand how persuasion is attempted in the social media environment, particularly as it impacts on issues of security. The first of these cases drew on 2218 Facebook posts to understand the Russian Internet Research Agency (IRA) campaign to influence the outcome of the 2016 US presidential elections. The findings highlight how a comprehensive understanding of the political and social cleavages within the US allowed the IRA to utilise both prosumer interaction in conjunction with the technical capabilities afforded by Facebook to co-construct persuasive arguments to carefully segmented audiences. This was designed to exploit the political and social cleavages, mobilise conservative voters while suppressing liberal voters and, ultimately, to shape the election outcome in a manner desirable to Russia. The second case drew on 2,473 tweets from Russia’s state media Twitter account @RT_Com to understand the campaign to influence the Western response to the 2022 Russian invasion of Ukraine. Findings from this case highlighted how nation states combine a deep understanding of the social environment with social media platform affordances as part of an increasingly hybrid approach to warfare. More specifically, this case highlights how social media campaigns are undertaken by nation states in support of military objectives by targeting foreign populations and, in doing so, disrupting the political and, thus, military decision making of an adversary. A separate study undertook a synthesis of the findings from each of the case studies to identify emergent patterns and divergences across the data. Through both inductive and abductive reasoning, the analysis generated theoretical insights and developed a revised rhetorical framework. This thesis advances persuasion research in the social media environment in three key areas. First, it highlights how social media is not simply a transmitter of persuasive messaging but, rather, it is a socio‑technical environment where persuasion is co‑constructed in a digital ecology through both human interaction and platform affordances. Second, that Aristotle’s rhetorical framework, reframed for the contemporary environment, offers a practical and useful analytical tool for understanding persuasive attempts via social media. Third, that when persuasion in the contemporary social media environment is understood via a rhetorical framework, the implications for security at the individual, societal, national, and international levels become clear.
Keywords: Aristotle; Rhetoric; Persuasion; Social Media; National Security; Political psychology; Rhetoric and psychology; Social media and war; Social media; Influence; Political aspects; 520505 Social psychology; 470101 Communication studies